Rafael Torres Sánchez. El precio de la guerra. El Estado fiscal-militar de Carlos III (1779-1783). Madrid, Marcial Pons, 2013, 459 págs. ISBN-10: 8492820926; ISBN-13: 978-8492820924. - Lanza, Ramón (Investigaciones de Historia Económica, 2019)
Sin resumen